3º) Calcule as raízes da função f(x) = -9x² + 6x - 1.
Soluções para a tarefa
Respondido por
1
Explicação passo-a-passo:
-9x² + 6x - 1 = 0
a= -9; b = 6; c = -1
D = 6² - 4 . -9 . (-1)
D = 36 - 36
D = 0
x' = (-6 + 0)/(2 . (-9))
x' = (-6 + 0)/(-18)
x' = (-6)/(-18)
x' = 1/3
x" = (-6 - 0)/(2 . (-9))
x" =( -6 - 0)/( -18)
x'' = (-6)/( -18)
x'' = 1/3
Perguntas interessantes
Física,
7 meses atrás
História,
7 meses atrás
Física,
7 meses atrás
Matemática,
8 meses atrás
Matemática,
8 meses atrás
Ed. Física,
1 ano atrás